Design and Implementation of Electricity Fault Detection System Using Microcontroller Arduino UNO - Chandra Adrian; Mia Galina (President University, 2021)
This paper concentrates of creating a fault detection system that detect both emergency fault and fault that need of maintenance with prototype of electrical installation that is done through manual simulation method. The prototype consists of the lamp as the load integrated with Arduino UNO as the microcontroller with GSM module and buzzer. The microcontroller will detect and deduce the type of the fault happened in the installation and will send the data of the fault through the GSM module. GSM module then transmits the data to the mobile phone and let the user aware of the fault. Also, there will be buzzer as the warning system by producing high pitch sound that signalizes the fault that need immediate handling or emergency. The data of both faults will be sent as Short Message Service (SMS) to the user. The SMS will give the user the type of fault either emergency or need of maintenance, happened in the installation.